Production of high protein fungal biomass in shrimp pond water : effects of intial sterilization - Nur Syafiqah, binti Mohamad Nasir (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Bioremediation process by using Rhizopus oligosporus is a potential method for shrimp pond water treatment. This approach seems to be a practical and inexpensive means of reducing the inorganic nitrogen in the pond. Through the subsequent uptake of nitrogen by the R. oligosporus, high protein fungal biomass (HPFB) can be synthesis and manufactured. Nitrogen control also induced by the addition of carbohydrates as a carbon added materials in SPW. The growth rate of R. oligosporus in SPW via submerge fermentation (SmF) with supplementation of 1.8% glucose solution as a carbon added materials was constantly increase in a6 days of fermentation. Based on the phenol-sulphuric analysis, there are 60% of total carbohydrate added being consumed by R. oligosporus. The study also showed that total nitrate and nitrite in SPW was reduced gradually for every 24 hours of fermentation. There are 98% of nitrate reduction and 100% of nitrite reduction by R. oligosporus in the sample during the fermentation stage. Effects of initial sterilization in SPW for HPFB production was tested using filtration, UV light and boiling method. The highest biomass production was notable at filtration parameter which is 2.96 g/L. This result may be explained that media pretreated with filtration method has no obvious effects in the substrate changes and nutrient reduction